2015
DOI: 10.1534/genetics.115.181289
|View full text |Cite
|
Sign up to set email alerts
|

Actin Cytoskeletal Organization in Drosophila Germline Ring Canals Depends on Kelch Function in a Cullin-RING E3 Ligase

Abstract: The Drosophila Kelch protein is required to organize the ovarian ring canal cytoskeleton. Kelch binds and cross-links F-actin in vitro, and it also functions with Cullin 3 (Cul3) as a component of a ubiquitin E3 ligase. How these two activities contribute to cytoskeletal remodeling in vivo is not known. We used targeted mutagenesis to investigate the mechanism of Kelch function. We tested a model in which Cul3-dependent degradation of Kelch is required for its function, but we found no evidence to support this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 75 publications
(108 reference statements)
4
51
0
Order By: Relevance
“…BTB‐Kelch proteins are characterized by the presence of an N‐terminal BTB domain and a C‐terminal Kelch domain, with a subset of BTB‐Kelch proteins containing a conserved intervening region of undetermined function, known as the BTB and C‐terminal Kelch (BACK) domain (Figure b; Stogios and Prive, ). BTB‐Kelch proteins bind a variety of substrates via their Kelch domains to regulate numerous cellular functions, including cell migration, gene expression, cytoskeletal rearrangement, and protein degradation (Bomont et al, ; Hudson et al, ; Kang et al, ; Nacak et al, ). The Kelch motif, which is approximately 44 to 56 residues in length, exists most often in four to seven tandem repeats (Bork & Doolittle, ; Xue & Cooley, ).…”
Section: Btb‐kelch Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…BTB‐Kelch proteins are characterized by the presence of an N‐terminal BTB domain and a C‐terminal Kelch domain, with a subset of BTB‐Kelch proteins containing a conserved intervening region of undetermined function, known as the BTB and C‐terminal Kelch (BACK) domain (Figure b; Stogios and Prive, ). BTB‐Kelch proteins bind a variety of substrates via their Kelch domains to regulate numerous cellular functions, including cell migration, gene expression, cytoskeletal rearrangement, and protein degradation (Bomont et al, ; Hudson et al, ; Kang et al, ; Nacak et al, ). The Kelch motif, which is approximately 44 to 56 residues in length, exists most often in four to seven tandem repeats (Bork & Doolittle, ; Xue & Cooley, ).…”
Section: Btb‐kelch Proteinsmentioning
confidence: 99%
“…The founding member of this family of proteins, the Drosophila Kelch protein, is required for the organization of actin‐rich ring canals, which are derived from arrested cleavage furrows and function as intercellular bridges to allow for the flow of essential factors from the nurse cells to the oocyte during oogenesis (Xue and Cooley, ). Recent work has demonstrated that the activity of Kelch in growth and organization of the ring canal cytoskeleton depends on its ability to bind Cul3, a component of the cullin‐RING E3 ubiquitin ligase (CRL) complex (Hudson & Cooley, ; Hudson et al, ). Cul3 proteins recruit BTB family proteins to E3 ubiquitin ligase complexes, where BTB family proteins function in substrate recognition, selectively recruiting target proteins for ubiquitination and subsequent degradation by the proteasome (reviewed in Petroski & Deshaies, ).…”
Section: Btb‐kelch Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ring canal is initially composed of contractile ring components such as Anillin, kinesin motor MKLP (mitotic kinesin-like protein, Pavarotti in Drosophila ), and Myosin II. As ring canals grow, these initial components disappear, whereas the core components of mature ring canals, such as Hts-RC and Kelch, are loaded onto the ring canals [1012]. The expansion of ring canals is critical for oocyte development by allowing for the intercellular transport of cytoplasmic materials from nurse cells to the oocyte.…”
Section: Mechanisms To Establish Germ Cell Connectivity: Ring Canal Amentioning
confidence: 99%
“…Also up-regulated are cell cycle (CBP) and cytokinesis (Kif3C, rempA, CG33521, Syn, and kel) proteins. The cytoskeleton protein kelch is important for ovarian nurse cell-to-oocyte transport and protein degradation, a function carried by another up-regulated gene, Spn77Bc, in accessory glands (Hudson et al 2015). Conversely, down-regulated genes producing piRNAs include BMP signaling molecules (the growth factor Dawdle [Alp23B] and several Gsts) known to control the cell cycle in fly gonads (Wang et al 2015a).…”
Section: The Pirna Pathway Promotes Proliferation Of Wrr-1 Cellsmentioning
confidence: 99%